1988
DOI: 10.1021/bi00415a007
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine hydrogen-bonding and environmental effects in proteins probed by ultraviolet resonance Raman spectroscopy

Abstract: Ultraviolet resonance Raman spectra with 229-nm excitation are reported for aqueous tyrosine and for ovomucoid third domain proteins from chicken [OMCHI3(-)] and from chachalaca [OMCHA(-)], as well as alpha 1-, alpha 2-, and beta-purothionin. At this excitation wavelength interference from phenylalanine is minimized, and it is possible to determine the frequencies of the Tyr ring modes nu 8a and nu 8b. The nu 8b frequency decreases with the degree of Tyr H-bond donation, reaching a limiting value for deprotona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
125
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(138 citation statements)
references
References 51 publications
12
125
1
Order By: Relevance
“…The decreased intensity of Tyr and Trp modes is consistent with T-state H-bond formation, as has been previously reported [58]. The intensity decrease of Phe modes in the T-state probably results from an increase in the solvent exposure of one or more Phe residues, since the intensities of some Phe vibrational modes are diagnostic of local environments, where a higher intensity is indicative of a more hydrophobic environment [34,35]. X-ray crystal structure determinations have suggested that the β85 Phe is more solvent exposed in the T-state, and the change in intensity is mainly attributed to that residue [3,59,60].…”
Section: Structure Of Nem-modified Hb S Probed By Uvrr Spectroscopysupporting
confidence: 87%
See 1 more Smart Citation
“…The decreased intensity of Tyr and Trp modes is consistent with T-state H-bond formation, as has been previously reported [58]. The intensity decrease of Phe modes in the T-state probably results from an increase in the solvent exposure of one or more Phe residues, since the intensities of some Phe vibrational modes are diagnostic of local environments, where a higher intensity is indicative of a more hydrophobic environment [34,35]. X-ray crystal structure determinations have suggested that the β85 Phe is more solvent exposed in the T-state, and the change in intensity is mainly attributed to that residue [3,59,60].…”
Section: Structure Of Nem-modified Hb S Probed By Uvrr Spectroscopysupporting
confidence: 87%
“…Spiro and coworkers have previously identified spectral features diagnostic of the critical α 1 β 2 interface [33], which are monitored as a function of quaternary state and fiber formation. In addition, Phe signals, reflective of local environment, increase in intensity with fiber formation, and are used as monitors of the fiber state [34,35]. Thus, one advantage of UVRR spectroscopy over other spectroscopic techniques is the ability to selectively probe both the α 1 β 2 subunit interface, and the intermolecular 1 β 1 -2 β 2 interaction that promotes Hb S fiber formation.…”
Section: Introductionmentioning
confidence: 99%
“…The main problem of dealing with equation 6 is that no analytic formulae for the electronic transition dipole moment, , are known. In order to overcome this limitation, is usually approximated as a Taylor series of the normal coordinates of the initial or intermediate electronic states about their respective equilibrium geometry as follows: (7) In the following derivation, we will consider only terms up to the first order. The zerothorder terms corresponds to the Franck-Condon approximation, while the inclusion of the first-order terms is known as the Herzberg-Teller approximation.…”
Section: Theory a General Theory Of Resonance-raman Spectroscopymentioning
confidence: 99%
“…Furthermore, only transitions between vibrational states of the initial and intermediate states corresponding to intense vibronic transitions are enhanced, and this makes RR spectra easier to interpret than nRR ones. As a result, it is possible to study specific regions in complex systems by tuning the incident radiation to match the energy of the electronic transition of interest 3,6,7 . For instance, the enhancement can be applied only on the peaks due to the vibrations of a chromophore in a biomolecule, eliminating the interference from the rest of the molecule, present in the nRR spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…UV-RRS was used to measure hydrophilic interactions, in particular the H-bond strength between water solvent molecules and the polar groups on the aromatic side chain. [4][5][6][7] RRS has also been used to investigate the interactions between metal atoms in metallo-enzymes [8][9][10] and nearby amino acid residues serving as coordinating ligands. [10][11][12] Moreover, RRS has been used for examining tertiary protein structure such as the α and ψ angles of the peptide linkages in proteins, 13 as well as the hydrophobicity around aromatic amino acid residues.…”
Section: Introduction Uv Resonance Raman Scattering (Rrs) Spectroscopmentioning
confidence: 99%